2003
DOI: 10.1007/s00414-003-0376-5
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation in dental pulp DNA based on human telomere shortening

Abstract: Age estimation based on evidence found in teeth has received considerable attention within the field of forensic science. We determined the terminal restriction fragment (TRF) length, as telomere length, to estimate age. Using dental pulp DNA we found the average TRF length showed a tendency to shortening with aging. Our findings show that telomere shortening, based on dental pulp DNA is a new and useful approach to estimate age of the subject at the time of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 20 publications
(25 reference statements)
1
49
0
1
Order By: Relevance
“…3), that may be caused by the complex effect of negative factors including IR influence. Our results correspond to the data [14], obtained at the study of TL of dental DNA of different age groups of patients (15-85 years), and the highest TL was found in molars.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…3), that may be caused by the complex effect of negative factors including IR influence. Our results correspond to the data [14], obtained at the study of TL of dental DNA of different age groups of patients (15-85 years), and the highest TL was found in molars.…”
supporting
confidence: 75%
“…In some of them, the associations of telomere length (TL) in adult patients were estimated, namely the TL from peripheral blood WBC in case of periodontal tissue lesions [12], TL of dental DNA depending on an age [12], depending on the age, gender, and type of teeth (molar ones etc.) [13], length of terminal restrictive fragment as the DNA TL analogue from dental pulp for age assessment [14]. The TL, telomerase and reverse transcriptase activity, surface antigens of papillary dental stem cells, pulp, follicles and mesenchymal stem cells from bone marrow [15] were assayed in comparative aspect in a favor of restorative dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, others used the Terminal Restriction Fragments (TRF) length method to measure the TL, as Tsuji et al (2002) and Takasaki et al (2003) in Japan; r = -0.832 and -0.749 respectively and p<0.01. Ren et al (2009) in China who recorded a correlation coefficient "r" value = -0.913 and p<0.01, Hewakapuge et al (2008) explained the differences in the observed "r" values as a result of differences in ethnicity, sample size, laboratory conditions in each study and not be due to differences in measuring TL in different methods.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is difficult to determine age by existing data. In addition, there is no research report of systemic population about telomere shortening (Takasaki et al, 2003;Ren et al, 2009). Saeed et al (2012) confirmed that it is necessary to design basic science experiments for better evaluation of the role of TL in molecular prediction of biological age, as it remains the most promising biomarker for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the length of telomeres decreases with age, presumably due to cell divisions -the more cell divisions, the shorter the telomere length -and, since the number of cell divisions increases with age, telomere length could be a proxy for age. 56 Indeed, several studies have shown this, [63][64][65][66] although telomere length is individual, and relies on genetic and environmental factors. The error given in studies is around ±10 years.…”
Section: Chemical and Molecular Biological Methodsmentioning
confidence: 99%